Variants in CCL16 are associated with blood plasma and cerebrospinal fluid CCL16 protein levels. (June 2016) - Ebbert, Mark; Staley, Lyndsay; Parker, Joshua; Parker, Sheradyn; Bailey, Matthew; Ridge, Perry; Goate, Alison; Kauwe, John
Abstract Background CCL16 is a chemokine predominantly expressed in the liver, but is also found in the blood and brain, and is known to play important roles in immune response and angiogenesis. Little is known about the gene's regulation. Methods Here, we test for potential causal SNPs that affect CCL16 protein levels in both blood plasma and cerebrospinal fluid in a genome-wide association study across two datasets. We then use METAL to performed meta-analyses with a significance threshold ofp  < 5x10−8 . We removed SNPs where the direction of the effect was different between the two datasets. Results We identify 10 SNPs associated with increased CCL16 protein levels in both biological fluids. Conclusions Our results will help understandCCL16 's regulation, allowing researchers to better understand the gene's effects on human health.